Repeated Impact-Based Capture of a Spinning Object by a Dual-Arm Space Robot - Nagaoka, Kenji; Kameoka, Ryota; Yoshida, Kazuya (Frontiers in Robotics and AI, 2018)
This paper presents detumbling and capture of space debris by a dual-arm space robot for active space debris removal missions. Space debris, such as a malfunctioning satellite or a rocket upper stage, often has uncontrolled tumbling motion. It also has uncertainties in its parameters, such as inertial characteristics or surface frictional roughness. These factors make the debris capture missions difficult to accomplish. To cope with such challenging missions, we propose a detumbling and capture control method for a dual-arm robot based on repeated impact capable of suppressing the debris motion by repeatedly utilizing an effect of a passive damping factor in the contact characteristics. In this paper, as the initial step of a study on the repeated impact-based capture method, we assume that the capture target is a rocket upper stage that can be simply modeled as a cylindrical body and mainly has angular velocity motion in its principle axis of inertia. A motion tracking control law of an end-effector of the robot arm is introduced to maintain the repeated impact. The proposed control method enables the robot to accomplish the detumbling and capture without precise estimation of the inertial characteristics and surface frictional roughness of the debris. The validity of the proposed method is presented by numerical simulations and planar microgravity experiments using an air-floating system. In particular, the experimental evaluation shows the fundamental feasibility of the proposed method, and thus, the result contributes to a practical application.